2005
DOI: 10.1051/animres:2005034
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dent versus flint maize genotype on site and the extent of starch and protein digestion, ruminal fermentation and microbial protein synthesis in the rumen of sheep

Abstract: -Ruminal and whole tract digestibility of protein and starch, microbial protein yield in the rumen and molar proportions of volatile fatty acids (VFA) in the rumen fluid and faeces were determined in sheep that were given either maize silage derived from the dent (DTS) or flint type hybrid (FTS). Degradabilities in the rumen were determined by means of the in sacco method using three sheep and microbial protein yield in the rumen by means of urinary purine derivative excretion using four sheep. The extent of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 38 publications
(55 reference statements)
2
3
3
Order By: Relevance
“…The atypical climate conditions in year 2012 may have enhanced the earliness-related differences in chemical composition between hybrids. The N content of the silages ranged from 1.2 to 1.3% of DM, and was similar among hybrids (as reported by Verbic et al, 2005). In agreement with a review by Khan et al (2015), and as already integrated in INRA (2007) feed tables, starch content increased and NDF and ADF contents decreased with increasing maturity for hybrid FD.…”
Section: Characteristics Of Whole-plant Corn Silagesupporting
confidence: 88%
See 1 more Smart Citation
“…The atypical climate conditions in year 2012 may have enhanced the earliness-related differences in chemical composition between hybrids. The N content of the silages ranged from 1.2 to 1.3% of DM, and was similar among hybrids (as reported by Verbic et al, 2005). In agreement with a review by Khan et al (2015), and as already integrated in INRA (2007) feed tables, starch content increased and NDF and ADF contents decreased with increasing maturity for hybrid FD.…”
Section: Characteristics Of Whole-plant Corn Silagesupporting
confidence: 88%
“…Fast starch fermentation has been shown to reduce ruminal pH, inhibit fiber digestibility, and thereby increase the risk of digestive disorders (Beauchemin and Yang, 2005). Studies exploring the variability of corn digestion in cattle have investigated the effects of genotype (Taylor and Allen, 2005;Verbic et al, 2005) and grain processing (Huntington, 1997;Johnson et al, 2002;Fernandez et al, 2004) on ruminal starch digestion measured in situ (Lopes et al, 2009;Ali et al, 2014) and in vitro (Tang et al, 2011;Opsi et al, 2013). However, most of the in vivo studies (Bal et al, 1997;Fernandez et al, 2004) available have focused on starch from concentrate-supplemented corn silage diets.…”
Section: Introductionmentioning
confidence: 99%
“…When compared to GS, a decrease of metabolizable protein concentration in GS-MS was mainly due to a decrease in the supply of postruminally digested dietary protein while GS-FB and in GS-M both, a decrease in the supply of postruminally digested dietary protein as well as a decrease in the supply of digestible true microbial protein, were observed. In absolute terms the metabolizable protein concentrations in diets from the present experiment are higher than those obtained for maize silage (Verbič et al, 2005) and considerably higher than for GS values reported by Verbič et al (1999).…”
Section: Metabolizable Protein and Nitrogen Balancecontrasting
confidence: 80%
“…Higher degradabilities are expected in silages made from dent type grain hybrids than in those characterised by the flint type grain (Verbič et al, 2005). Despite the fact that in the present experiment MS was made of flint type hybrid, EDGCP was closer to the value reported for silage from dent type hybrid (Verbič et al, 2005). The EDGCP of FB was slightly lower than what was reported by Hvelplund and Weisbjerg (2000) (880 g kg -1…”
Section: Degradability Of Feeds and Diets In The Rumencontrasting
confidence: 64%
See 1 more Smart Citation